Attractiveness of Facial Symmetry in the Context of the Dominant Visual Field (European Journal of Behavioral Sciences, 2023)
One of the key features of an attractive face is symmetry. The presence of symmetry in living organisms reflects their ability to cope with various adverse environmental or genetic factors, thus a symmetrical face signals the hidden qualities of the organism. Despite the evolutionary basis for the attractiveness of facial symmetry, studies that have examined it have yielded diverse results. One reason may lie in the fact that the symmetrical stimulus faces are often composites that are created by using the mirror image of one, which can lead to contradictory outcomes. When evaluating human faces, the dominance of the left visual field (as a reflection of brain lateralisation functions) comes into play, which may modify the attractiveness of the composite depending on whether it was created as a left-sided mirror image (using the left half of the face) or a right-sided mirror image (using the right half of the face). The study aims to evaluate the attractiveness of left-sided and right-sided symmetrical facial composites and how the evaluator's visual field dominance affects the assessed attractiveness. The research was conducted on a sample of 1,921 participants aged from 15 to 77 (M = 23.57; SD = 9.52); 60.7% women using computerised facial composites in quasi-experimental research design. The results show that left-sided facial composites are significantly (p